2012
DOI: 10.1038/ajg.2012.335
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota of De-Novo Pediatric IBD: Increased Faecalibacterium Prausnitzii and Reduced Bacterial Diversity in Crohn's But Not in Ulcerative Colitis

Abstract: The gastrointestinal microbiota is considered important in infl ammatory bowel disease (IBD) pathogenesis. Discoveries from established disease cohorts report reduced bacterial diversity, changes in bacterial composition, and a protective role for Faecalibacterium prausnitzii in Crohn ' s disease (CD). The majority of studies to date are however potentially confounded by the effect of treatment and a reliance on established rather than de-novo disease. METHODS:Microbial changes at diagnosis were examined by bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
180
8
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(203 citation statements)
references
References 46 publications
(36 reference statements)
9
180
8
5
Order By: Relevance
“…Given their widespread association with a variety of different environments, including dairy, meat, vegetable, and grain-fermented foods and as commensals in the gastrointestinal tract, this genus has been widely consumed and also has been used in dietary supplements to promote general health and well-being (21)(22)(23). Recent human microbiome studies have identified Faecalibacterium prausnitzii as an organism with antiinflammatory properties and have reported it to be an indicator microbial population that was lowered in subjects with Crohn's disease and ulcerative colitis (10,24). In addition to GOS, reported herein, Faecalibacterium also has been shown to be stimulated by the fructooligosaccharide inulin, and specific strains are reported to grow in host-derived substrates such as N-acetylglucosamine (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given their widespread association with a variety of different environments, including dairy, meat, vegetable, and grain-fermented foods and as commensals in the gastrointestinal tract, this genus has been widely consumed and also has been used in dietary supplements to promote general health and well-being (21)(22)(23). Recent human microbiome studies have identified Faecalibacterium prausnitzii as an organism with antiinflammatory properties and have reported it to be an indicator microbial population that was lowered in subjects with Crohn's disease and ulcerative colitis (10,24). In addition to GOS, reported herein, Faecalibacterium also has been shown to be stimulated by the fructooligosaccharide inulin, and specific strains are reported to grow in host-derived substrates such as N-acetylglucosamine (25).…”
Section: Discussionmentioning
confidence: 99%
“…Genera in cluster I, interpreted as taxa suppressed by GOS and dairy, included genera in Enterobacteriaceae, Streptococcus, Clostridium, Lachnospira, Anaerotruncus, Ruminococcus, and others. Cluster II, interpreted as taxa enhanced in the long term by GOS, included the health-promoting genera Lactobacillus and Faecalibacterium; the latter was found at lower population levels in individuals with inflammatory bowel diseases (9,10). Also enhanced in population were Christensenellaceae (Christensenellaceae_other), a poorly defined family enriched in individuals with a low body mass index (BMI).…”
Section: Impact Of Gos On the Composition And Function Of The Gut Micmentioning
confidence: 99%
“…A permutational multivariate analysis of variance (adonis) quantified the reported p-values for the null hypothesis that the PCA axes are not different by group based on 1e4 permutations. These trends are also observed in an independent analysis of the MetaHIT cohort (S11 Fig). research on separate cohorts also found that the community structure of biopsy-associated microbiomes [46][47][48] differed substantially between UC and CD patients, with UC appearing more like controls in the latter two; one study also saw similar trends in functional annotation from shallow shotgun sequencing [46]. UC and CD can also be differentiated serologically, with UC tending to be characterized more by autoantibodies directed at host neutrophils [49] [50], though these may arise through cross-reactivity with microbial proteins like OmpC [51], and CD being characterized more by antibodies against cell-surface glycans [52], Saccharomyces cerevisiae [50], and proteins such as flagellin [53].…”
Section: Accurate Metagenome Annotation Clarifies Community Functionamentioning
confidence: 99%
“…To ensure we capture the greatest diversity of bacterial species and their encoded effector functions in our metagenomic library collection, we created metagenomic libraries using DNA isolated from the stool of a healthy patient, a patient with Crohn's disease, and a patient with ulcerative colitis. Crohn's disease and ulcerative colitis are collectively known as inflammatory bowel disease (IBD), and bacterial populations in each of these diseases are unique relative to each other and to patients without IBD (12,(27)(28)(29).…”
Section: Significancementioning
confidence: 99%